1998
DOI: 10.1007/bf03339983
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Parental Bonding Instrument to compare interpretations of the parental bond by adolescent girls with restricting and binge/purging anorexia nervosa

Abstract: The Parental Bonding Instrument (PBI) was administered to 62 adolescent female patients (mean age 14.3): 35 with restricting-type anorexia nervosa (RAN), and 27 with binge/purging-type anorexia nervosa (B/PAN) according to the DSM-IV criteria, all at onset and initial diagnosis. The PBI was also administered to a control group (55 subjects) and 22 patients with Crohn's disease or celiac disease. The three groups were matched for age and socioeconomic status. The RAN and B/PAN patients gave significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
4
12
1
1
Order By: Relevance
“…Comparing with healthy controls and patients with other mental disorders, patients with anorexia nervosa perceive higher levels of parental care and lower levels of overprotection by their mothers (Russell et al 1992). With regards to restricting type and binge/purging type of anorexia nervosa, the parental bonding is perceived as more inadequate (espe-cially in case of fathers) in the latter group (Di Pentima et al 1998). It has been shown that this inadequacy is previous to the onset of the anorexia nervosa.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparing with healthy controls and patients with other mental disorders, patients with anorexia nervosa perceive higher levels of parental care and lower levels of overprotection by their mothers (Russell et al 1992). With regards to restricting type and binge/purging type of anorexia nervosa, the parental bonding is perceived as more inadequate (espe-cially in case of fathers) in the latter group (Di Pentima et al 1998). It has been shown that this inadequacy is previous to the onset of the anorexia nervosa.…”
Section: Introductionmentioning
confidence: 97%
“…1992). With regards to restricting type and binge/purging type of anorexia nervosa, the parental bonding is perceived as more inadequate (especially in case of fathers) in the latter group (Di Pentima et al . 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Parental lack of flexibility and pronounced dominance of one member over others may reinforce both control and perfectionism, typical features of ED patients (Westerberg, Edlund, & Ghaderi, 2008) and could impair parents' responsiveness to counselling. On the other hand, families characterised by enmeshment and scarce empathy may show hyper protection and carelessness (Di Pentima et al, 1998;Fassino et al, 2010;Fosse & Holen, 2006;Sordelli, Fossati, Devoti, La Viola, & Maffei, 1996), resulting in a lack of responsiveness to family treatments.…”
Section: Predictors Of Response To Counselling Interventionmentioning
confidence: 98%
“…2014, Keating ve ark. 2013, Tasca ve Balfour 2014) çok az sayıda çalışma AN olan ergenlerde bağlanma güvenliğini araştırmıştır (Di Pentima ve ark. 1998, Balottin ve ark.…”
unclassified